2021
DOI: 10.1136/bmjopen-2021-053248
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial transparency and data sharing among biopharmaceutical companies and the role of company size, location and product type: a cross-sectional descriptive analysis

Abstract: ObjectivesTo examine company characteristics associated with better transparency and to apply a tool used to measure and improve clinical trial transparency among large companies and drugs, to smaller companies and biologics.DesignCross-sectional descriptive analysis.Setting and participantsNovel drugs and biologics Food and Drug Administration (FDA) approved in 2016 and 2017 and their company sponsors.Main outcome measuresUsing established Good Pharma Scorecard (GPS) measures, companies and products were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In our study, only 32% of evaluated pharmaceutical companies outside the top 20 by global revenue had a publicly accessible data sharing policy, which is in stark contrast to 100% of sponsors within the top 20 by global revenue. These findings are in line with previous research and demonstrate a continued need for advocacy and support for smaller pharmaceutical companies to enable data transparency. Despite their lower revenue, these smaller companies anchor the registration of a substantial portion of critical innovator medicines in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 32% of evaluated pharmaceutical companies outside the top 20 by global revenue had a publicly accessible data sharing policy, which is in stark contrast to 100% of sponsors within the top 20 by global revenue. These findings are in line with previous research and demonstrate a continued need for advocacy and support for smaller pharmaceutical companies to enable data transparency. Despite their lower revenue, these smaller companies anchor the registration of a substantial portion of critical innovator medicines in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…However, rejecting the patient–industry complex position is unwarranted as it has never specified a necessary share of financially dependent organisations. Moreover, as we have mentioned, the possibility of under‐reporting of financial links remains and cannot be discounted, especially in view of ongoing concerns that clinical trials are massively underreported in the pharmaceutical sector, although larger companies are typically more compliant with reporting requirements (Axson et al, 2021; Goldacre et al, 2018). That said, our data suggest that likely pockets of a patient–industry complex exist in the subsection of organisations highly reliant on industry funding.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this paper, to develop measures of fair inclusion in clinical research, was identified and developed during a roundtable that JM organized in 2017 with patients and patient advocacy groups (participant list was previously published). 21 A patient advocacy organization (Susan G Komen Foundation) then sponsored this study and is an acknowledged contributor. In June 2022, we held a 7 hour roundtable with approximately 40 individuals representing research sponsors (online supplemental box 2) on these measures, with majority if not unanimous agreement on their reasonableness and appropriateness.…”
Section: Patient and Public Involvementmentioning
confidence: 99%